Evaluation of valuation of toxicity profile of an alkaloidal fraction of the stem bark of picralima nitida (fam. apocynaceae) (2004)
Dermal and acute toxicity evaluation of the basic alkaloidal fraction of the stem bark of Picralima nitida, which has been shown to have pronounced activity against causative organisms of dermatomycosis in man, was carried out in animals. Acute intraperitoneal toxicity tests showed a dose-dependent toxicity. There was inflammation and necrosis of liver hepatocytes accompanied by reduction in neutrophilic count and a corresponding increase in lymphocytic count. There was no sign of reddening or irritation when applied into the eye conjunctiva. Dermal tests also showed that the fraction caused no sensitization, inflammation or death in the animal models used.